METODE PENGOLAHAN AIR LIMBAH ALTERNATIF UNTUK NEGARA BERKEMBANG - Satoto E. Nayono (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2010)
Domestic or industrial wastewater management and treatment in many developing countries tend to imitate the systems and technology from industrialized countries by adopting a centralized wastewater processing system and treatment technologies such as activated sludge or tertiary nutrients removal. However, the effort to replicate these methods, in fact, is not an appropriate solution to overcome the problems of sanitation in developing countries, particularly Indonesia. These sophisticated technologies require a large energy supply, skilled operators as well as substantial operating costs.Furthermore, these methods do not provide any opportunity to recover energy and valuable nutrients contained in wastewater. These reasons can cause wastewater management become unsustainable. This paper will present some alternatives and concepts in the management and treatment of wastewater. It will be limited to several natural wastewater treatment alternatives to support sustainable management of water resources in terms of both technology and financing. Some low-cost appropriate technologies for wastewater treatment will also be discussed include: anaerobic treatment, wastewater treatment by waste stabilization ponds, wastewater treatment by macrophytes ponds and wastewater treatment by constructed wetlands.Keywords: wastewater, natural wastewater treatment, anaerobic treatment, waste stabilization ponds, macrophytes ponds, constructed wetlands